To express the recursively defined sequence using function notation correctly based on the given information, we analyze the definitions first:
- The initial condition is given as \( a_1 = -3 \).
- The recursive definition states \( a_n = a_{n-1} + 4 \).
The closest match from the options involves function notation using \( f \), where:
- \( f(1) = -3 \): This corresponds to the initial value \( a_1 = -3 \).
- \( f(n) = f(n-1) + 4 \): This corresponds to the recursive relationship \( a_n = a_{n-1} + 4 \).
Thus, the correct representation in function notation would be:
f(1) = -3; f(n) = f(n-1) + 4
So the correct response is:
f(1)=−3; f(n)=f(n−1)+4